Effects of Historical Coercive Control, Historical Violence, and Lawyer Representation on Post-Separation Male Partner Violence Against Mother Litigants Who Participated in Adversarial Family Court Proceedings - Ellis, Desmond (Violence against women, 2021)
The primary objective of this study was to test the effects of historical male partner violence and lawyer representation on post-separation male partner violence and coercive control against mother litigants participating in adversarial family court proceedings. Toward this end, staff at two women’s shelters administered a questionnaire to 40 former residents who met the sample selection criteria. Two findings are noteworthy. First, there was a decrease in mother litigant reports of post-separation physical violence requiring a visit to a hospital. Second, post-separation male partner coercive control “most/some of the time” was reported by 97.5% of all 40 separated mother litigants who also reported experiencing historical coercive control by their male partners. Recommendations and limitations are described in the final two pages.